Implementing routine outcome monitoring in clinical practice: Benefits, challenges, and solutions - Boswell, James F.; Kraus, David R.; Miller, Scott D.; Lambert, Michael J. (Psychotherapy research, 2015)
This article reviews the benefits, obstacles, and challenges that can hinder (and have hindered) implementation of routine outcome monitoring in clinical practice. Recommendations for future routine outcome assessment efforts are also provided. Spanning three generations, as well as multiple developed tools and approaches, the four authors of this article have spent much of their careers working to address these issues and attempt to consolidate this learning and experience briefly here. Potential "elephants in the room" are brought into the discussion wherever relevant, rather than leaving them to obstruct silently the field's efforts. Some of these topics have been largely ignored, yet must be addressed if we are to fulfill our promise of integrating science and practice. This article is an attempt to identify these important issues and start an honest and open dialogue.